1999
DOI: 10.1083/jcb.145.6.1209
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Differentiation of Oligodendrocytes Requires Activation of Fyn Tyrosine Kinase

Abstract: In the central nervous system, myelination of axons occurs when oligodendrocyte progenitors undergo terminal differentiation and initiate process formation and axonal ensheathment. Although it is hypothesized that neuron-oligodendrocyte contact initiates this process, the molecular signals are not known. Here we find that Fyn tyrosine kinase activity is upregulated very early during oligodendrocyte progenitor cell differentiation. Concomitant with this increase is the appearance of several tyrosine phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
215
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(236 citation statements)
references
References 35 publications
18
215
2
1
Order By: Relevance
“…Fyn is a member of the Src family of kinases and is associated with cell adhesion, migration, proliferation, differentiation, apoptosis and cytoskeletal rearrangements (Osterhout et al, 1999). Increased phosphorylation of Fyn following MAG cross-linking in double-transfected COS cells has been reported previously (Umemori et al, 1994;Umemori et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Fyn is a member of the Src family of kinases and is associated with cell adhesion, migration, proliferation, differentiation, apoptosis and cytoskeletal rearrangements (Osterhout et al, 1999). Increased phosphorylation of Fyn following MAG cross-linking in double-transfected COS cells has been reported previously (Umemori et al, 1994;Umemori et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Fyn is a key molecule in OLG differentiation and myelination (Osterhout et al, 1999;Sperber and McMorris, 2001;Umemori et al, 1994). This molecule belongs to the Src (Rous sarcoma) family of kinases and is associated with cell migration, proliferation, differentiation, adhesion, apoptosis and cytoskeletal rearrangements (Osterhout et al, 1999).…”
Section: Initial Axon-glial Contactmentioning
confidence: 99%
“…This molecule belongs to the Src (Rous sarcoma) family of kinases and is associated with cell migration, proliferation, differentiation, adhesion, apoptosis and cytoskeletal rearrangements (Osterhout et al, 1999). …”
Section: Initial Axon-glial Contactmentioning
confidence: 99%
“…8 Hypomyelination of the optic nerve is significantly increased by ~40-50% in Fyn-deficient mice and by ~80% in MAG/ Fyn-deficient mice. 21,22 PTPα is a physiological activator of Fyn as demonstrated by the 60% reduced kinase activity of Fyn in brains of PTPα-deficient mice compared with WT mice.…”
Section: Methodsmentioning
confidence: 99%
“…7 Given that F3 is located at paranodes and promotes oligodendrocyte maturation as well as acts as a binding partner of PTPα, and that Fyn is implicated in oligodendrocyte differentiation and myelination, [8][9][10] we hypothesized that PTPα might be involved in modulating paranodal formation and myelination during CNS development. In this study, we found that PTPα was mainly expressed in both neurons and oligodendrocytes.…”
Section: Introductionmentioning
confidence: 99%